2012
DOI: 10.1007/s10658-012-9955-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sanitation processes on survival of Synchytrium endobioticum and Globodera rostochiensis

Abstract: The two quarantine pests Synchytrium endobioticum, the causal agent of potato wart disease and Globodera rostochiensis, the yellow potato cyst nematode are currently present in Germany. Winter sporangia of Synchytrium endobioticum and cysts of Globodera rostochiensis can be spread with waste from potato processing industries, if infected tubers are processed. The German Biowaste Ordinance prescribes sanitation of organic waste before it can be used on arable land as fertilizer or filling material. Sanitation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Steinmöller et al . () reported that viable winter sporangia (resting spores) of S. endobioticum could be confirmed in sample material using microscopy and plant bioassays after composting for 70 days at 30–45 °C, 21 days at 50–55 °C or 12 days at 60–65 °C. However, conclusions from the two methods did not correlate and bioassay results were variable.…”
Section: Introductionmentioning
confidence: 97%
“…Steinmöller et al . () reported that viable winter sporangia (resting spores) of S. endobioticum could be confirmed in sample material using microscopy and plant bioassays after composting for 70 days at 30–45 °C, 21 days at 50–55 °C or 12 days at 60–65 °C. However, conclusions from the two methods did not correlate and bioassay results were variable.…”
Section: Introductionmentioning
confidence: 97%
“…Finally, organic waste from processing has to be sanitized before it can be used as fertilizer in agriculture, in horticulture, or in private gardens, for instance by composting or pasteurization (EPPO, 2008). While these techniques have been proven effective against plant pests such as potato cyst nematodes, they have little to no effect on the resting sporangia of S. endobioticum (Steinmöller et al, 2012). Moreover, composting of infected potato material is part of the inoculum preparation for Spieckermann assays (EPPO, 2004).…”
Section: Distribution Dispersal and Disease Managementmentioning
confidence: 99%
“…discarded potatoes, soil, water) from potato processing industries used as fertiliser, land fill or irrigation water (Efremenko and Yakovleva, 1981;Langerfeld, 1984;Steinm € oller et al, 2004). Potato processing is an important industrial sector in many EU MSs, including Germany, where 3 million tonnes of waste are produced of which the major part is used as fertiliser (Steinm € oller et al, 2012).…”
Section: Eu Distribution Of Main Host Plantsmentioning
confidence: 99%